Pemanfaatan Biji Kelor Sebagai Bahan Baku Pembuatan Tempe - Klarisa Fransiska Dhenggo; Yoseph Jhon; kartini Rahman Nisa (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Moringa is a plant that is easy to grow in the tropics, with a slightly bitter taste that is neutral and non-toxic. This plant is commonly used as a hedge plant and its leaves are used as a vegetable. Apart from Moringa leaves, Moringa seeds are also used as a food ingredient, one of which is tempeh. However, some raw materials can also be used to make tempeh, for example soybeans and jackfruit seeds. Moringa seeds contain many bioactive compounds that are beneficial for health and Moringa seed extract provides a protective effect that reduces liver lipid peroxide and is antihypertensive. With these advantages, Moringa seeds have the potential to be used as raw material for making tempeh